Bridging the gap in sustainable radiography: insights from five countries in Asia and Africa - Mohamed Abuzaid; Nora Almuqbil; Christian Ven Emery; Wiam Elshami; Manal Ibham; Naifah Alsubaie; Zuhal Hamd; Mohamed Aljamal (BMC Health Services Research)
Abstract Introduction Sustainability in healthcare, particularly in medical imaging, is increasingly important as healthcare operations contribute significantly to global emissions. Radiographers, as integral members of imaging departments, play a vital role in implementing sustainable practices. This study examines radiographers’ perceptions, practices, and barriers to sustainability across five countries: the United Arab Emirates, Saudi Arabia, Palestine, Sudan, and Ghana, highlighting regional differences and factors influencing engagement. Methods A cross-sectional survey was conducted among 441 radiographers using an online platform. The survey included questions on demographic information, sustainability perceptions, practices, and barriers. Data were analyzed using descriptive statistics and the Kruskal-Wallis H test to evaluate regional variations in sustainability engagement. Results Results revealed moderate sustainability knowledge among participants, with 45.1% (n = 199) understanding the concept and 46.7% (n = 206) recognizing its benefits. Common practices included digital documentation (34.6%, n = 289) and daily energy reduction efforts (32.2%, n = 142). However, advanced practices such as recycling residual contrast media or adopting energy-efficient equipment were limited. Key barriers included lack of training (39.2%, n = 173), financial constraints (44.7%, n = 197), and insufficient managerial support (39.2%, n = 173). Regional variations were evident, with Ghana showing the highest engagement across knowledge, attitudes, and practices, while Saudi Arabia scored the lowest. Statistical analysis indicated significant differences in sustainability engagement by region (p < 0.05), with Ghana benefiting from targeted educational initiatives and international collaborations. In contrast, resource limitations and insufficient institutional support hindered progress in other regions. Conclusion The findings emphasize the need for tailored strategies to promote sustainability in radiography. Recommendations include integrating sustainability into radiography curricula, providing targeted training, enhancing leadership support, and adopting region-specific interventions. Addressing these challenges can empower radiographers to contribute to environmentally sustainable healthcare systems.